Strategi Pengembangan Usaha Budidaya Lebah Madu Kelulut Kelompok Usaha ‘Pasir Puti’ Di Desa Petak Puti Kecamatan Timpah Kabupaten Kapuas - Rinaldi Aria Chandra; Kuwing Baboe; Windy Utami Putri (FKIP, Universitas Palangka Raya, 2022)
In establishing a business, it is needed to have the right strategy in developing its business. In Petak Puti Village, Timpah District, Kapuas Regency, there is a kelulut honey bee cultivation business,that is run by the “PASIR PUTI” Business Group. The purpose of this study is to describe and determine the strategy for developing the kelulut honey bee cultivation business that is carried out by the “PASIR PUTI” Business Group in Petak Puti Village, Timpah District, Kapuas Regency. The method is used in this research, it is descriptive-qualitative method, where the researcher describes a phenomenon according to the actual situation and presents it in the words based on the results of data collection. The types of data are used, they are primary data and secondary data. The data collection consists of observation, interviews, and documentation. The data analysis was carried out in three stages sequentially, they are data reduction, data presentation, and drawing conclusions. The results showed that factors influence the development of the kelulut honey bee cultivation business group “PASIR PUTI” in Petak Puti Village, Timpah District, Kapuas Regency, there were two factors, they are supporting factors and inhibiting factors. The supporting factors are the existence of permits to carry out business group organizational activities, having business group assistants as well as business partners, and promising business group income. While the inhibiting factors are the erratic weather around the location of kelulut honey bee cultivation, the presence of pests from kelulut honey bees, and the lack of skills from the group members in handling post-harvest honey bees. In carrying out the strategy for developing the kelulut honey bee cultivation business, the “PASIR PUTI” Business Group develops initial products by adding stup and planting flower plants that produce pollen to become additional feed for kelulut honey bees, in addition to natural food from the forest around Petak Puti Village. Furthermore, in handling post-harvest, kelulut bee honey products are marketed through business assistants as well as business partners. In pricing, the price of the product offered is sometimes uncertain. The promotion is done through the word of mouth. And the product distribution still uses travel services.